Combination of Mucuna bracteata Mulch and NPK-Biofertilizer for Taro (Colocasia esculenta L.) Vegetative Growth - Dini, Isna Rahma; Hapsoh, Hapsoh; Manurung, Kezia Eunika (Universitas Panji Sakti, 2026)
Taro (Colocasia esculenta L.) is a tuber crop with high economic value and potential as an alternative food source, yet its productivity remains low due to declining soil fertility and low organic matter content. This study aimed to evaluate the effect of Mucuna bracteata organic mulch combined with reduced NPK fertilizer dosage and biofertilizer application on the vegetative growth of taro. The experiment was conducted at the Experimental Garden of the Faculty of Agriculture, University of Riau, from May to August 2025 using a non‑factorial Completely Randomized Design with five treatments and four replications. Observed parameters included leaf stalk length, number of leaves, leaf area, leaf area index, stem diameter, chlorophyll content, soil temperature, and soil moisture. The results indicated that 75% and 50% NPK fertilizer combined with biofertilizer and M. bracteata mulch produced vegetative growth comparable to that of 100% NPK fertilizer across most parameters. The use of M. bracteata mulch and biofertilizer reduced inorganic NPK fertilizer requirements by 25–50% without decreasing vegetative growth.